Pengaruh Pengembangan Kapasitas, Mentoring Dan Motivasi Terhadap Pemberdayaan Sumber Daya Manusia Bidang Pariwisata Di Wilayah Kecamatan IV Koto Kabupaten Agam - Putra, Ricky Eka; Hasan, Alizar (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
IV Koto District is one of the 16 sub-districts in Agam Regency which has 7 Nagari and 24 Jorong. The purpose of this research is to determine the role of the sub-district government in providing capacity development, mentoring and motivation in efforts to increase human resource empowerment in the tourism sector in the IV Koto sub-district area, Agam Regency. The population in the study was the entire Nagari Subdistrict IV Koto, Agam Regency, totaling 156 people. Samples were searched using the Slovin formula, resulting in a sample of 61 people. The data analysis technique uses SEM-PLS analysis. The research results show a positive and significant influence of capacity development on HR empowerment in the Nagari Sector IV Koto District, Agam Regency. There is a positive and insignificant influence of mentoring on HR empowerment in the Nagari Sector IV Koto District, Agam Regency. There is a positive and significant influence of motivation on HR empowerment in the Nagari Sector IV Koto District, Agam Regency.